Relative Income Position and Performance: An Empirical Panel Analysis - Benno Torgler; Sascha L. Schmidt; Bruno S. Frey (Fondazione Eni Enrico Mattei (FEEM), 2006)
Many studies have established that people care a great deal about their relative economic position and not solely, as standard economic theory assumes, about their absolute economic position. However, behavioral evidence is rare. This paper provides an empirical analysis on how individuals relative income position affects their performance. Using a unique data set for 1114 soccer players over a period of eight seasons (2833 observations), our analysis suggests that the larger the income differences within a team, the worse the performance of the soccer players is. The more the players are integrated in a particular social environment (their team), the more evident this negative effect is.
Keywords: D00; D60; L83; 330; Relative Income; Positional Concerns; Envy; Performance; Social Integration; Einkommensverteilung; Leistungsmotivation; Fußballsport; Panel; Soziale Beziehungen